The effects of cinnamon supplementation on adipokines and appetite-regulating hormones: A systematic review of randomized clinical trials - Alireza Gheflati; Naseh Pahlavani; Elyas Nattagh-Eshtivani; Zahra Namkhah; Mohammad Ghazvinikor; Golnaz Ranjbar; Mostafa Shahraki Jazinaki; Abdolreza Norouzy (Mashhad University of Medical Sciences, 2023)
Objective: Cinnamon is extracted from the inner bark of Cinnamomum trees. Recent studies have indicated that cinnamon is a safe and cost-effective treatment for improving body weight, lipid profiles, insulin resistance, and blood pressure. This systematic review aimed to summarize the effect of cinnamon supplementation on adipokines and appetite-regulating hormones.Materials and Methods: This comprehensive literature search was conducted using databases such as PubMed, Scopus, ISI Web of Science, and Google Scholar up to March 2022 without any limitation. The quality of eligible studies was evaluated through the Cochrane Collaboration's tool for assessing the risk of bias.Results: This systematic review included six clinical trial studies (363 participants), among which, only one study was performed on children, and two investigations were conducted on obese participants. A decreasing effect was found in the level of leptin and visfatin after cinnamon supplementation. Two out of three studies examined adiponectin levels and revealed non-significant effects of cinnamon consumption on this parameter. Two studies evaluated ghrelin levels and found an increase after cinnamon supplementation. The result of cinnamon supplementation on other biomarkers such as glucose-dependent insulinotropic polypeptide, glucagon-like peptide 1, and resistin was inconsistent.Conclusion: The result of this systematic review indicated the increasing effect of cinnamon supplementation on ghrelin levels and decreasing effect on leptin and visfatin levels. However, more clinical data are required to clarify the beneficial effects of cinnamon on adipokines levels due to the controversial findings of the studies.